2017
DOI: 10.1021/acs.jpca.7b09440
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Cobalt–Corrole–Pyridine Complexes: Noninnocent Five-Coordinate Co(II) Corrole–Radical States

Abstract: Two sets of complexes of Co-triarylcorrole-bispyridine complexes, Co[TpXPC](py) and Co[BrTpXPC](py) have been synthesized, where TpXPC refers to a meso-tris(para-X-phenyl)corrole ligand with X = CF, H, Me, and OMe and BrTpXPC to the corresponding β-octabrominated ligand. The axial pyridines in these complexes were found to be labile and, in dilute solutions in dichloromethane, the complexes dissociate almost completely to the five-coordinate monopyridine complexes. Upon addition of a small quantity of pyridine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 62 publications
(128 reference statements)
7
69
0
Order By: Relevance
“…In the polar CDCl 3 solvent, broad signals were obtained for 1NH 3 which contains two electron‐withdrawing Cl substituents on the meso ‐phenyl rings (Figure 5c), but almost no signal is observed for 4NH 3 which bears electron‐donating substituents (Figure 5f). The lack of a diamagnetic spectrum for 4NH 3 is consistent with a dissociation of one or both labile NH 3 ligands in CDCl 3 , generating a paramagnetic form of the cobalt corrole due to the non‐innocent character of the four‐ or five‐coordinate species . However, when NH 3 gas was bubbled into the NMR tube, broad signals appeared for 4NH 3 (Figure 5e) indicating a mixture of electronic spin states for the cobalt ion ( S = 0, diamagnetic and S = 1, paramagnetic), as well as some S = 1/2 species probably due to traces of the corrole radical.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…In the polar CDCl 3 solvent, broad signals were obtained for 1NH 3 which contains two electron‐withdrawing Cl substituents on the meso ‐phenyl rings (Figure 5c), but almost no signal is observed for 4NH 3 which bears electron‐donating substituents (Figure 5f). The lack of a diamagnetic spectrum for 4NH 3 is consistent with a dissociation of one or both labile NH 3 ligands in CDCl 3 , generating a paramagnetic form of the cobalt corrole due to the non‐innocent character of the four‐ or five‐coordinate species . However, when NH 3 gas was bubbled into the NMR tube, broad signals appeared for 4NH 3 (Figure 5e) indicating a mixture of electronic spin states for the cobalt ion ( S = 0, diamagnetic and S = 1, paramagnetic), as well as some S = 1/2 species probably due to traces of the corrole radical.…”
Section: Resultsmentioning
confidence: 66%
“…In order to confirm the paramagnetic behavior of these complexes, EPR experiments were run on the electron‐poor and electron‐rich 1NH 3 and 4NH 3 complexes in toluene at 293 K (Figures S9 and S10), and this data should give a direct measurement of the electronic spin state . In both cases, the spectra (Figures S9a and S10a) have a radical‐like pattern centered at g = 2.002, with a small broadening of the single line (FWHH ≈ 10 G).…”
Section: Resultsmentioning
confidence: 99%
“…The cobalt is coordinated in a distorted octahedral environment with axial elongation of the Co−N bonds to the pyridine molecules. The Co−N distances lie in the range of reported bond distances for corrole complexes with low-spin Co(III) centers 32 (Figure 2, top, all potentials are reported vs the FcH + /FcH couple), one quasireversible reduction at −0.77 V, and an irreversible reduction at −2.06 V. On the basis of our EPR spectroscopic measurements, DFT calculations, and previously reported studies, 4,23 we assigned the first and second oxidations to corrole centered processes and the first reduction to the Co(III)/Co(II) redox couple. The quasi-reversibility of the latter process is due to the dissociation equilibrium of one apical pyridine ligand, which has been extensively studied by Kadish et al 34,35 Upon an increase in the scan rate ( Figures S23 and S24), the first reduction becomes more irreversible, Figure 1.…”
Section: Inorganic Chemistrymentioning
confidence: 68%
“…In general, the redox processes of 1Py 2 and 2Py 2 are observed at 200−400 mV more negative potentials than the ones observed for Co(tpfc), 14,38 and they lie in a similar range to the redox potentials of reported Co[TpXC]Py 2 corroles (TpXC = 5,10,15-tris(pX-phenyl)corrole; pX = p-CF 3 , p-H, p-Me, and p-OMe substituents). 32 On the other hand, cobalt corroles with alkyl and aryl D substituents in β-positions are much easier to oxidize than the meso-substituted corroles here described. This is to be expected given the electron-donating effect of the alkyl substituents.…”
Section: Inorganic Chemistrymentioning
confidence: 79%
“…The sterically hindered TMP ligands was chosen to improve the stability of the Cr(IV) complex, but the differences in peripheral transition metal d electron counts, XAS has only been infrequently applied to Cr porphyrins and indeed to metalloporphyrin-type complexes in general, except for those involving Mn and Fe. [1][2][3][4][5][6][7][8] Indeed, only one directly relevant study has been reported in the literature, focusing on Cr IV [TTP]O and Cr V [TTP]N, where TTP 2À is the dianion of meso-tetra(p-tolyl) porphyrin. 9 Understandably, we have used substantially improved theoretical methods in the present study to model the Cr K-edge XAS data on the high-valent compounds 2 and 3, and where appropriate, we will point out similarities and differences relative to the earlier study.…”
Section: Introductionmentioning
confidence: 99%